2007
DOI: 10.1016/j.bbadis.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme enhancement activity of N-octyl-β-valienamine on β-glucosidase mutants associated with Gaucher disease

Abstract: Gaucher disease (GD), caused by a defect of beta-glucosidase (beta-Glu), is the most common form of sphingolipidosis. We have previously shown that a carbohydrate mimic N-octyl-beta-valienamine (NOV), an inhibitor of beta-Glu, could increase the protein level and enzyme activity of F213I mutant beta-Glu in cultured GD fibroblasts, suggesting that NOV acted as a pharmacological chaperone to accelerate transport and maturation of this mutant enzyme. In the current study, NOV effects were evaluated in GD fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…We have previously demonstrated the effectiveness of chemical chaperone therapy in G M1 -gangliosidosis, [58,59] Gaucher disease [20,21] and Fabry's disease. [60] Notably, we recently found that chaperone therapy can prevent neurological deterioration in a G M1 -gangliosidosis model mouse expressing R201C mutant human b-galactosidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated the effectiveness of chemical chaperone therapy in G M1 -gangliosidosis, [58,59] Gaucher disease [20,21] and Fabry's disease. [60] Notably, we recently found that chaperone therapy can prevent neurological deterioration in a G M1 -gangliosidosis model mouse expressing R201C mutant human b-galactosidase.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical chaperone activity in Gaucher disease (GD) mutants has been reported for several N-substituted derivatives of the carbasugar b-valienamine [21,46] and of the iminosugar 1-deoxynojirimycin (DNJ), [26,27,47,48] among which the N-(n-nonyl) derivative (NN-DNJ). Recently, we found that bicyclic sp 2 -iminosugar analogues of the parent alkaloid nojirimycin (NJ), with structure of 5-N,6-X-(N'-alkyliminomethylidene)nojirimycin (X represents O, S or N) behaved as very selective competitive inhibitors of b-glucosidases, including human b-glucocerebrosidase.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesized mechanism of action for these compounds is competitive binding to the active site of the mutant enzyme, facilitating proper folding and trafficking to the lysosome, where endogenous substrate displaces the chaperone and enzyme activity is restored (8,13,15). Most GC chaperones studied to date are enzyme inhibitors in the structural class of iminosugars or similar analogs of the natural substrate, glucosylceramide (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Iminosugars have been shown to increase the cellular activity of the N370S mutant form of GC, as well as of wild-type enzyme (15,26).…”
mentioning
confidence: 99%
“…Although an increase in cellular activity has been demonstrated by several groups using a variety of competitive inhibitors [66][67][68][69], the exact mechanism by which these compounds exert their effect is not firmly established. A similar increase in activity can be achieved following treatment of macrophages with NN-DNJ and uptake of Cerezyme through the mannose receptor [70].…”
Section: Future Therapiesmentioning
confidence: 99%